Transfusion associated graft-versus-host disease (TA-GVHD) in an immunocompetent patient following orthopedic surgery - (:unkn) unknown (My University, 2006)
Transfusion associated Graft versus Host Disease (TA-GVHD) is a well-known but rare complication that follows infusion of histo-incompatible lymphoid cells, often seen in individuals with impaired cellular immunity. However, it may also occur in immunocompetent individuals. The clinical syndrome consists of fever, skin rash, diarrhea, hepatic dysfunction, and bone marrow aplasia. The outcome is nearly always fatal. We present here a case report of fatal TA-GVHD in a "presumed" immunocompetent patient after transfusion of whole blood from a first and a second degree relative following orthopedic surgery for right coxarthrosis.
Keywords: Immunocompetent; Rash; Transfusion-associated graft versus host disease